2017
DOI: 10.1111/aas.13045
|View full text |Cite
|
Sign up to set email alerts
|

The adequate rocuronium dose required for complete block of the adductor muscles of the thigh

Abstract: Although the response of the adductor pollicis muscle to rocuronium cannot be used to determine the adequate rocuronium dose required for complete block of the thigh muscles, intense blockade, with maintenance of post-tetanic count at ≤ 1 in the adductor pollicis muscle is essential to prevent the obturator jerk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Another potential explanation for the observed lack of benefit from deep NMB in this patient population may be differential effects of NMB on different muscle groups in the body. One recent study which examined the rocuronium dose required to block direct obturator nerve stimulation of adductor muscles of the thigh found that complete blockade of the thigh adductors was achieved before TOF count responses in the adductor pollicis were suppressed [12]. We measured depth of NMB at the adductor pollicis and thus cannot rule out the possibility that the response of this muscle to NMB may have differed to the response of muscles, affecting the operative site during minimally invasive ALTHA.…”
Section: Discussionmentioning
confidence: 91%
“…Another potential explanation for the observed lack of benefit from deep NMB in this patient population may be differential effects of NMB on different muscle groups in the body. One recent study which examined the rocuronium dose required to block direct obturator nerve stimulation of adductor muscles of the thigh found that complete blockade of the thigh adductors was achieved before TOF count responses in the adductor pollicis were suppressed [12]. We measured depth of NMB at the adductor pollicis and thus cannot rule out the possibility that the response of this muscle to NMB may have differed to the response of muscles, affecting the operative site during minimally invasive ALTHA.…”
Section: Discussionmentioning
confidence: 91%
“…Second, the present study was limited to studying the effect of moderate neuromuscular blockade on the transition of ventilatory leak and sealing pressure. There are situations when the surgeon asks for the patient to be even more relaxed which may lead to intense neuromuscular blockade (eg preventing the obturator jerk during transurethral resection of bladder tumours) when utilizing a supraglottic airway device 23 . Consequently, studies investigating the correlation between higher doses of rocuronium and the transition of sealing pressures are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Этого добиться практически невозможно даже при наличии мониторинга нервно-мышечной проводимости и достаточного выбора мышечных релаксантов. По данным большинства исследователей, рефлекс запирательного нерва сохраняется даже в условиях общей анестезии с мышечными релаксантами [7][8][9][10].…”
Section: Discussionunclassified